2008
DOI: 10.1007/978-3-540-89652-4_62
|View full text |Cite
|
Sign up to set email alerts
|

Market Overview of Enterprise Mashup Tools

Abstract: Abstract.A new paradigm, known as Enterprise Mashups, has been gain momentum during the last years. By empowering actual business end-users to create and adapt individual enterprise applications, Enterprise Mashups implicate a shift concerning a collaborative software development and consumption process. Upcoming Mashup tools prove the growing relevance of this paradigm in the industry, both in the consumer and enterprise-oriented market. However, a market overview of the different tools is still missing. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 6 publications
0
75
0
1
Order By: Relevance
“…A number of surveys and reviews aimed at analyzing current mashup development approaches and tools have been reported in recent years (e.g., [2,9,10,14]). …”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of surveys and reviews aimed at analyzing current mashup development approaches and tools have been reported in recent years (e.g., [2,9,10,14]). …”
Section: Related Workmentioning
confidence: 99%
“…Hoyer and Fischer [10] presented a market overview of the different mashup composition tools by classifying and evaluating them according to several perspectives such as general information, functionality and usability. They classified more than 30 tools in their proposed classification model in order to draw market trends in context of Enterprise mashups.…”
Section: Related Workmentioning
confidence: 99%
“…With this annotation, we are describing the message in terms of an OWL class in an existing ontological model. This message is set as an output of the "pubCityState" operation in a portType (lines [18][19][20][21][22] and included in a portlet type binding (lines [23][24][25][26][27][28][29][30][31][32][33][34][35]. The "pubCityState" operation corresponds to broadcasting the city and state information to PropertyBroker.…”
Section: Semantic Annotation Of Componentsmentioning
confidence: 99%
“…As a number of research works suggest [32], [28], [33], [34], most tools provide limited search and discovery for mashup components. Users still need to know how to write code (e.g., JavaScript or XML/HTML) and link the components using technical concepts derived from programming.…”
Section: Related Workmentioning
confidence: 99%
“…In general, two different mashup types are dominant [4]: Consumer mashups are mostly for private use, combining data from several resources by unifying them using a common interface. Enterprise mashups combine different sources (content, data or application functionality) from at least one resource in an enterprise environment.…”
Section: Introductionmentioning
confidence: 99%